Efficacy of budesonide suspension in the treatment of lobar pneumonia by fiberoptic bronchoscopic alveolar lavage - Ji, Xin; Fu, Hongjie; Zhang, Fang; Chen, Na; Xing, Xiugui; Ji, Jinghua; Zhou, Tian; Song, Xiangqin (Frontiers in Medicine, 2025)
ObjectiveTo probe the efficacy of budesonide suspension in treating lobar pneumonia by fiberoptic bronchoscopic alveolar lavage.MethodsA total of 176 preschool and school-age children with lobar pneumonia in the pediatric respiratory department of Binzhou Medical University Hospital from December 2020 to December 2021 were selected and divided into observation group (OG, n = 88) and control group (CG, n = 88) based on the wishes of their families. Children in both groups were given azithromycin sequential treatment. The CG was given fiberoptic bronchoscope alveolar lavage with sodium chloride injection, and the OG was treated with fiberoptic bronchoscope alveolar lavage with sodium chloride injection + inhalation of budesonide suspension. The treatment, inflammatory factor levels, immune function, lung function indicators, adverse reactions and clinical efficacy were compared between both groups.ResultsThe total effective rate of the OG was 90.91%, which was better than 81.82% of the CG (χ2 = 3.095, p < 0.05). After treatment, the serum IL-6, CRP and ESR levels declined, and IL-2 level was elevated in the OG relative to the CG (p < 0.05). The levels of IgM, IgA, IgG, FVC, FEV1, PEF, FEF25, FEF50, FEF75 and FEF25-75 in the OG were enhanced compared to the CG (p < 0.05). The antipyrexia time, the disappearance time of lung shadow, the improvement time of cough and expectoration, and the disappearance time of lung rales in the OG were shorter compared to the CG (p < 0.05).ConclusionBudesonide combined with fiberoptic bronchoscopy lavage in treating lobar pneumonia in children with Mycoplasma pneumoniae is effective in enhancing the therapeutic effect, relieving the clinical symptoms and signs of children faster, significantly reducing the inflammatory response, and significantly improving lung function. It is safe, effective and has no adverse reactions.